Pirolisis Kayu Ketapang (Terminalia Catappal) Menjadi Bio-Oil Dengan Katalis Mo/Lempung Cengar - Feby Pratama Nugraha; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The demand for renewable energy to adequate human energy continue to increase. Currently, the main energy source in the world is a fossil fuel. So, we need alternative energy instead of petroleum. Biomass can be used as a bio-oil by pyrolysis. The wood can be used as raw materials of bio-oil is not a superior product and its rapid growth, these requirements exist in ketapang tree (Terminalia catappa L.).The purpose of this research is to make bio-oil from ketapang tree using a catalyst Mo/clay by pyrolysis process, as well as test physical properties of the bio-oil, and to determine the effect of variation the carrier of the catalyst metal catalyst weight variations against of biomass. In this research ketapang tree by the size of -100+200 mesh, 50 grams, 500 ml silinap and catalyst Mo / clay inserted into of pyrolysis reactor. This process conducted at a temperature 320oC and the stirring speed of 300 rpm operate for about 120 minutes by flowing nitrogen gas. For the optimum yields obtained at 1.5% catalyst Mo/clay as much as 7% of biomass that is equal to 70,35%. The test results physical properties obtained density of 1.005 g/ml, 2.14 cSt viscosity, acidity 46.17 mg NaOH /g sample and the flash point 49oC. Results of analysis compound chemical using GC-MS, obtained the dominant chemical components in the bio-oil is Methyl 2-Hydroxybutyrate (16,79%); Methyl acetate (5,66%); 1-hydroxy-,2-Propanone (12,96%) ; Acetic acid (31,53%).Keywords: biomass, bio-oil, catalyst mo/clay, ketapang,Terminalia Catappa, pyrolysis